A Survey of Demographics and Treatments in Melanoma Case Reports: Retrospective Bibliometric Analysis - Ross O'Hagan; Jessie Ngandjui; Benjamin Ungar; Jonathan Ungar; Nicholas Gulati (JMIR Publications, 2024)
Melanoma case reports show variations in treatment by age and sex.